2011
DOI: 10.1007/s10750-011-0601-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fossil chironomid remains along a depth gradient: evidence for common faunal thresholds within lakes

Abstract: Many environmental variables that are important for the development of chironomid larvae (such as water temperature, oxygen availability, and food quantity) are related to water depth, and a statistically strong relationship between chironomid distribution and water depth is therefore expected. This study focuses on the distribution of fossil chironomids in seven shallow lakes and one deep lake from the Plymouth Aquifer (Massachusetts, USA) and aims to assess the influence of water depth on chironomid assembla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 55 publications
8
64
2
Order By: Relevance
“…Langdon et al (2006) assessed the relationships between chironomids and water quality in 57 different lakes, and concluded that the biological communities responded to nutrient change although not always directly. Seven shallow lakes and one deep lake were investigated by Engels & Cwynar (2011) to determine the sensitivity of chironomids to water depth. Different taxa showed their specific water depth in these USA lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Langdon et al (2006) assessed the relationships between chironomids and water quality in 57 different lakes, and concluded that the biological communities responded to nutrient change although not always directly. Seven shallow lakes and one deep lake were investigated by Engels & Cwynar (2011) to determine the sensitivity of chironomids to water depth. Different taxa showed their specific water depth in these USA lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the influence of water depth on midge distribution can be detected from lake surface sediment data of fossils collected using site-specific (intralake), local, and regional data sets (Korhola et al 2000;Kurek, and Cwynar 2009b;Luoto 2009aLuoto , 2010Engels, and Cwynar 2011). Kurek and Cwynar (2009b) showed significant differences in the performance statistics of North American site-specific, local, and regional training sets implying differences in taxa optima through spatial scales.…”
Section: Introductionmentioning
confidence: 98%
“…The influence of water depth is mostly indirect and mediated through habitat distribution, such as availability of macrophytes and the type of substrate, which have been found to be of direct importance for midges (Learner et al 1989;Nyman et al 2005). Fossil remains of midges, mostly Chironomidae, usually accumulate close to their living habitats (Eggermont et al 2007;Kurek, and Cwynar 2009a;Luoto 2010Luoto , 2011Engels, and Cwynar 2011). Hence, it is possible to use these fossil assemblages to infer past changes in their habitats from downcore sediment profiles.…”
Section: Introductionmentioning
confidence: 99%
“…For the past 20 years, sub-fossil chironomids preserved in lake sediments have started to be used in paleolimnology to quantitatively reconstruct various factors such as nutrients (Lotter et al, 1998), macrophytes (Langdon et al, 2010), salinity (Heinrichs et al, 1999), lake depth (Engels and Cwynar, 2011), anoxia (Quinlan et al, 1998) and temperature (Larocque-Tobler et al, 2011). As they are becoming accurate indicators (Brooks et al, 2012), their distribution is being studied in many parts of the world because new training sets are being developed for quantitative reconstruction.…”
Section: Introductionmentioning
confidence: 99%